G172(P) Improvement in motor function after growth hormone replacement in children with growth hormone deficiency and developmental delay. (24th May 2017) - Joy, R; Mathew, V; Jose, S; Gupta, S
Abstract : Introduction: Growth hormone has been proven to improve lean body mass and muscle strength. We report three cases where growth hormone replacement had a significant effect on gross motor function. Case series: A 15 month old boy was born at 33 weeks of gestation. During infancy, he was noted to have global developmental delay secondary to cerebral atrophy and isolated growth hormone deficiency. He was not able to pull himself to standing position but after commencing growth hormone replacement, he demonstrated a dramatic improvement in his gross motor skills and was able to stand independently and walk with support. A 4 year old boy with global developmental delay and was unable to stand independently. On investigation for short stature, he was noted to have isolated growth hormone deficiency and was commenced on growth hormone replacement. Three months later, he was noted to have made significant improvement in his muscle tone and general alertness. He was able to walk unaided for short distances. A 10 year old boy with developmental delay and isolated growth hormone deficiency was commenced on growth hormone replacement at a small dose in January 2015. At his next neurology review ten months later, he was able to walk unaided for short distance with an associated improvement in his muscle tone. The growth hormone dose was later increased to the standard dose. At his most recent review in July 2016, he was walking well independently and had an improved sleep pattern. Conclusions: Our case series demonstrates that growth hormone treatment in children with combination of growth hormone deficiency and gross motor delay could significantly improve gross motor function.